Common fixed-point theorems and c-distance in ordered cone metric spaces - Rahimi, H.; Soleimani Rad, G. (Український математичний журнал, 2013)
We present a generalization of several fixed and common fixed point theorems on c -distance in ordered cone metric spaces. In this way, we improve and generalize various results existing in the literature.